2012
DOI: 10.1021/ja309632m
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly Resolved Images of Peptide-Functionalized Gold Surfaces by Scanning Tunneling Microscopy

Abstract: Peptide-terminated monolayers were formed through a Huisgen cycloaddition reaction between an α-helical peptide containing two propargylglycine unnatural functional groups 20 Å apart and an alkanethiol self-assembled monolayer (SAM) on a gold surface containing 25% surface density of reactive azide terminal groups. The azide- and peptide-terminated surfaces were imaged by scanning tunneling microscopy (STM) using a low tunneling current of 10 pA. On the peptide-terminated surface, oblong features ~30 Å long an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 33 publications
3
30
0
Order By: Relevance
“…18,19 In particular, it is well-known that sequences containing both C α -tetrasubstituted and C α -trisubstituted α-amino acids promote the formation of 3 10 -helical structures for peptides shorter than 7-8 units, while a conformational transition to α-helical structures arises in longer sequences. 20,21 The inclusion of one Adt residue every three amino acids in a short peptide rich in C αtetrasubstituted residues should locate the dithiolane side chains in the correct positions to anchor the peptide chain cooperatively to the gold surface. We therefore synthesized a hexapeptide, denoted as Fc-CO-6Adt2, formed by two Adt-Ala-Aib triads and functionalized with an electroactive ferrocenoyl (Fc) group at the N-terminus (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In particular, it is well-known that sequences containing both C α -tetrasubstituted and C α -trisubstituted α-amino acids promote the formation of 3 10 -helical structures for peptides shorter than 7-8 units, while a conformational transition to α-helical structures arises in longer sequences. 20,21 The inclusion of one Adt residue every three amino acids in a short peptide rich in C αtetrasubstituted residues should locate the dithiolane side chains in the correct positions to anchor the peptide chain cooperatively to the gold surface. We therefore synthesized a hexapeptide, denoted as Fc-CO-6Adt2, formed by two Adt-Ala-Aib triads and functionalized with an electroactive ferrocenoyl (Fc) group at the N-terminus (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…This value falls within the range of densities reported elsewhere on various substrates, ranging from femto [44][45][46] to picomoles per mm 2 . 29,[47][48][49] We then found that the EO 7 -SVV surface had a significant impact on HUVEC adhesion and proliferation. We also found that this effect was specifically due to the presence of SVVYGLR since surfaces presenting the bioactive RGD peptide performed significantly less well than EO 7 -SVV surfaces.…”
Section: Discussionmentioning
confidence: 79%
“…Using complementary surface analysis techniques we were able to quantify the surface density of SVVYLGR which stands at 1.6 ± 0.2 pmol per mm 2 . This value falls within the range of densities reported elsewhere on various substrates, ranging from femto to picomoles per mm 2 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports confirm the effective modification of the gold substrate with peptides but little to no information is given on the quantitative evaluation of surface density [ 56 58 ]. In contrast, when quantifying surface density is possible using STM on atomically smooth gold, it is difficult to implement this type of substrate for biological experiments [ 59 ]. Others were able to quantify the interparticle distance of large dendrimers on gold by AFM [ 60 ] but since RGD clustering is known to strongly impact cell adhesion[ 61 ], the technique described by Lagunas et al .…”
Section: Discussionmentioning
confidence: 99%